The island city of Tinnīs : a postmortem - Gascoigne, Alison L., (Fouilles de l'Institut français d'archéologie orientale du Caire ;, 2020)
"On an island in Lake Manzala in the north-east corner of the Nile Delta lie the ruins of the once-prosperous late Roman and medieval port and manufacturing centre of Tell Tinnīs. Although little can be seen above ground, beneath the surface lie archaeological deposits that can be accessed by geophysical and geoarchaeological survey, and remote sensing. In addition, some excavation has taken place, providing evidence for the existence of structures such as cisterns, while ceramics and artefacts from the site's surface provide indications of the lifestyles of the town's occupants and their regional connections. This volume presents the results of archaeological work undertaken at the site between 2004 and 2012, which has produced a relatively detailed impression of the form and nature of the town from its inception around the 3rd century AD to its abandonment in the 13th century in the face of Crusader raids. This new information is discussed in light of the town's relationship to and connectedness with its surrounding landscape, and likewise considers Tinnīs in comparison to contemporary settlements of Egypt's Mediterranean coast"--Page 4 of cover.